PELATIHAN PEMBUATAN GOOGLE FORM UNTUK PENDATAAN PENDUDUK DESA DUKUH YANG TERDAMPAK COVID-19 - Rahayu, Cicilia Puji; Nugroho, Supriyana; Surendra, Arya; Budiwinarto, Kim; Wibowo, Ari (Fakultas Ekonomi Universitas Surakarta, 2024)
Abstract During the Covid-19 pandemic, all lines had to do 3M, namely washing hands, wearing masks and maintaining distance. The policy taken by the government during the Covid-19 pandemic was that all citizens were required to work from home to anticipate the spread of the virus. One of the impacts of this policy is the decline in the community's economy, so the government provides assistance to the community to help the economy. In order to receive this assistance, the Dukuh Village government must collect data on its residents affected by Covid-19. The data collection process cannot be carried out face to face and most Dukuh Village officials are not yet able to take advantage of technological advances. This is motivation for the service team to help provide solutions by holding training on creating Google forms for Dukuh Village officials as a medium for collecting data on residents affected by CoViD-19. The aim of providing this training is so that the Dukuh Village Government can obtain valid data and continue to follow the health protocols set by the government. The hope is that the expertise possessed by Dukuh Village officials can then be used for other purposes according to the needs of the village government. Keywords : Google Form, Pendataan, Desa Dukuh, CoViD-19